2017
DOI: 10.1083/jcb.201611061
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 regulates junctional actin but not cell polarization in the Caenorhabditis elegans epidermis

Abstract: Adherens junction remodeling allows changes in cell shape and position. Zilberman et al. show through live imaging that CDC-42 is dispensable for epithelial cell polarization, but its RhoGAP-regulated activity is needed to control junctional actin organization during embryo elongation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 96 publications
(165 reference statements)
6
41
0
Order By: Relevance
“…In contrary, our studies showed that electrostatic binding to PI4P and PIP2 alone is sufficient to localize aPKC/Par-6 to the PM without interacting with additional proteins such as Cdc42. Our results are consistent with findings that removing Cdc42 in C. elegans late embryos or in Drosophila pupal epithelial cells does not severely disrupt aPKC and Par-6 localization (Georgiou et al, 2008;Zilberman et al, 2017). Although mechanisms governing the aPKC/Par-6 subcellular localization appear to be heavily cell-type specific and multi-layered, our results highlight that the electrostatic PM-binding property of aPKC needs to be taken into consideration when studying the protein regulators of aPKC/Par-6 subcellular localization.…”
Section: Electrostatic Binding To Phosphoinositides By Polybasic Psr supporting
confidence: 91%
“…In contrary, our studies showed that electrostatic binding to PI4P and PIP2 alone is sufficient to localize aPKC/Par-6 to the PM without interacting with additional proteins such as Cdc42. Our results are consistent with findings that removing Cdc42 in C. elegans late embryos or in Drosophila pupal epithelial cells does not severely disrupt aPKC and Par-6 localization (Georgiou et al, 2008;Zilberman et al, 2017). Although mechanisms governing the aPKC/Par-6 subcellular localization appear to be heavily cell-type specific and multi-layered, our results highlight that the electrostatic PM-binding property of aPKC needs to be taken into consideration when studying the protein regulators of aPKC/Par-6 subcellular localization.…”
Section: Electrostatic Binding To Phosphoinositides By Polybasic Psr supporting
confidence: 91%
“…Interestingly, we find that ABpl's anterior cell-cell contact shows significantly higher HMR-1/E-cadherin levels than the posterior, which can explain the observed anterior PAC-1 enrichment ( Figure 5E). We can only speculate that this asymmetric localization of PAC-1 might also contribute to enhanced levels of cell-cell contact F-actin and reinforce recruitment of cell-cell adhesion proteins as described for late stages of embryonic morphogenesis (Zilberman et al, 2017).…”
Section: Role Of Rho Gtpases and Their Regulators In Pcpsupporting
confidence: 53%
“…Recent studies by several groups suggest that besides CED-10/ Rac1, the GTPases RHO-1 and CDC-42 also contribute to the morphogenetic process of ventral enclosure (Ouellette et al, 2016;Walck-Shannon et al, 2016;Wernike et al, 2016;Zilberman et al, 2017). However, cytoskeletal consequences of altering RHO-1 or CDC-42 function during ventral enclosure are poorly understood.…”
Section: Introductionmentioning
confidence: 99%